Special cutaneous vascular elements in one-humped camel (Camelus dromedarius) (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The aim of this study was to investigate the histomorphological structure and functional significance of various special regulatory devices of the vascular terminal branches of the skin in one-humped camel (Camelus dromedarius).Materials and methods: Skin samples from different body parts (e.g., front, neck and shoulder, back, belly, chest, thigh, flank and tail) of camel were used in this study. The samples were stained with Harris hematoxylin and trichrome stain. Semithin sections were also prepared from these samples.Results: The vascular elements demonstrated in the current study included- throttle arteries within the dermis on the level of the hair papillae, glomus bodies within the dermis on the level mid-length of the hair follicles, medium-sized arteries on the level of the secretory end-pieces of the epitrichial sweat glands, and tufts of spirally-oriented arterioles in the nearby of the hair follicles.Conclusions: These vascular elements are either designed to control blood pressure (Hemo-dynamic mechanism) or patterned to control body temperature (Thermo-regulatory mechanism).http://doi.org/10.5455/javar.2016.c137